Exploring the Impact of Using Instagram to Develop Saudi EFL Learners' Vocabulary - Maha Saad Alotaibi (Journal Corner of Education, Linguistics, and Literature, 2023)
The current paper aims to investigate the impact of using Instagram to develop vocabulary among Saudi EFL learners. With a descriptive research design, this paper filled a gap in the literature by examining the role of Instagram in building vocabulary among Saudi EFL learners. Therefore, quantitative and qualitative methods were employed. To collect data, the researcher used an online questionnaire and two different types of interviews. The online questionnaire included both closed-ended and open-ended questions, involving 217 Saudi EFL learners. Regarding the interviews, structured interviews were carried out with six Saudi EFL learners to collect detailed information. Additionally, to acquire more information, semi-structured interviews involved four English tutors on Instagram. As a result, the findings revealed that Instagram plays a key role in developing EFL learners' English vocabulary and can be used as a tool to expand their vocabulary. The findings of this study add to prior research in related fields and serve as a resource for researchers studying English language instruction and acquisition as well as EFL learners.